A misplaced central line: arterial blood gas sample, venous pressure trace and the tip within the lung. Issue 1 (21st May 2015) - Singh, Shivinder; Lamba, Navdeep Singh; Aggarwal, Naveen; Manrai, Kavita; Mohan, Sanil; Garg, Anurag
Summary: A 24‐year‐old male was scheduled for excision of a cerebellopontine angle tumour. The left internal jugular vein was cannulated preoperatively. The post procedure chest X‐ray showed the tip of the cannula in the left upper zone of the lung; however, blood could be freely aspirated and the transducer trace indicated a mean pressure of 5 mmHg. Blood gas analysis revealed a PaO2 of 13.6 kPa. Angiography confirmed the patients had partial anomalous pulmonary venous drainage with the tip of the catheter situated in the left upper pulmonary vein.